The Sanchez family: Mexican American high school and collegiate wrestlers from Cheyenne, Wyoming - Iber, Jorge, author; University of Wyoming Press, publisher (Colorado State University. Libraries, 2025)
The Sanchez Family is a family history detailing the Sanchez family's experiences as immigrants to Wyoming and the ways that their US-born children's interest in wrestling had cascading impacts across generations. By focusing on a sport and a state that have not received much attention, Jorge Iber conveys the importance of athletics as a part of the educational experience of the Latino community. The first members of this particular Sanchez clan arrived in Wyoming during the early decades of the twentieth century. The first-generation American grandchildren of these families—Gilbert, David, Arthur, and Ray—used wrestling to radically alter their social and economic status by attending college with athletic scholarships, graduating, and moving on to professional, middle-class careers. Subsequent generations of the family followed their fathers and uncles to the mats at various institutions, also going on to earn degrees and enter professional occupations. Indeed, Iber contends that wrestling became the family's "business," the mechanism by which the Sanchezes extricated themselves from Cheyenne's working class. Revealing a previously unstudied aspect of Mexican American life in the state, The Sanchez Family sheds light on another vehicle for the educational, social, and economic advancement of Latinos in other parts of the United States. The first book to examine the role of wrestling in the lives of Mexican Americans, it serves as a foundational text for Latino studies of sports and constructing racial counterscripts.
The Sanchez Family Arrives and Settles in Cheyenne: 1915-1956 -- Athletics/Sports as a Part of the Latino/a Historical Literature -- The Sanchez Name Begins to Stand Out in State Wrestling Circles: 1956-1967 -- Ray Sanchez Has a Brilliant Future: 1962-1981 -- The Next Generation of Sanchezes as Wrestlers and Coaches: 1979-2023 -- Conclusion: The Most Recent Generation of Sanchezes on the Mat and the Significance of Sport in Latino/Hispanic History and Life.
Keywords: Sanchez family; College athletes -- Wyoming -- Cheyenne; High school athletes -- Wyoming -- Cheyenne; Mexican Americans -- Wyoming -- Cheyenne; Wrestlers -- Wyoming -- Cheyenne